Methodology of Teaching the Topic "Getting to Know Representatives of Lycopodiaceae" (Texas Journal of Agriculture and Biological Sciences, 2023)
The article helps students to understand, facilitate and consciously, independently master the topic of Lycopodiopsida in practical training classes in the department of systematics of higher plants in botany. The representatives of this section are among the oldest plants among the higher plants, and they developed well on the earth at the end of the Paleozoic era. Currently, there are more than a thousand types of herbaceous representatives of them in the world. Among the species of Kazilma there are also large trees.